A study on bone mineral density in newly detected hyperthyroid patients - DR.E.DHIVYA,; DR.K.H.NOORUL AMEEN, (International Journal of Pharma and Bio Sciences, 2018)
Osteoporosis affects almost one in two Indian women older than 50 years of age. Thyroid disease is one of the most common endocrine problems.The prevalence of these two medical problems is on the rise.Hyperthyroidism is associated with accelerated bone remodeling, reduced bone density, osteoporosis, and an increase in fracture rate. To evaluate the bone mineral density in newly detected hyperthyroid patients. The study population comprised of 40 female patients with newly detected hyperthyroidism, before initiating therapy, aged between 21-65years,at Sree Balaji Medical College &Hospital, Chennai.Study Design included biochemical test Free T4 and TSH and assessment of Bone Mineral Density using Dexa Scan. In our study, the population was divided into two groups-premenopausal and postmenopausal.The premenopausal group had reduced BMD in the form of osteopenia only which was more pronounced at the femoral neck.The postmenopausal group, reduced BMD was in the form of both osteopenia and osteoporosis, more pronounced at the lumbar spine.Hyperthyroidism should be considered an important risk factor for osteoporosis and its prompt recognition and treatment is necessary to maintain bone health.